2019
DOI: 10.1002/rmb2.12286
|View full text |Cite
|
Sign up to set email alerts
|

The success of various endometrioma treatments in infertility: A systematic review and meta‐analysis of prospective studies

Abstract: Background Endometriosis is seen in 0.5%‐5% of fertile and 25%‐40% of infertile women. To investigate this conflict between gynecologists that ovarian endometriomas should be removed or not before making any decision about pregnancy among infertile women, the authors decided to carry out a systematic review and meta‐analysis to compare the effect of various available therapeutic methods and notice the impact of these options on women's pregnancy rate. Methods This review is based on PRISMA recommendations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 49 publications
2
19
0
3
Order By: Relevance
“…If considering only spontaneous conception, in our study the postoperative pregnancy rate for all infertile patients was 45.3%, which is consistent with data reported in the recent meta-analysis by Alborzi et al [28]. Moreover, our results showed slightly lower rates of spontaneous pregnancy after CO 2 laser vaporization compared to cystectomy (35.9% vs 55.5%, respectively); however, this finding did not reach statistical significance.…”
Section: Figsupporting
confidence: 88%
See 1 more Smart Citation
“…If considering only spontaneous conception, in our study the postoperative pregnancy rate for all infertile patients was 45.3%, which is consistent with data reported in the recent meta-analysis by Alborzi et al [28]. Moreover, our results showed slightly lower rates of spontaneous pregnancy after CO 2 laser vaporization compared to cystectomy (35.9% vs 55.5%, respectively); however, this finding did not reach statistical significance.…”
Section: Figsupporting
confidence: 88%
“…Noteworthy, our rates are also higher compared with those reported for patients with untreated endometrioma undergoing ART as a first approach (pregnancy rate: 35.1%) [27]. These results support other published data [28,29] and suggest that surgery is a good option in infertile women with endometrioma to improve their chances to get pregnant. These findings are likely related to the operator expertise in endometriosis surgery in our study that performed the procedures and to the improvement of techniques and instrumentation over time.…”
Section: Figsupporting
confidence: 85%
“…There was no difference among groups. However, the success rate of surgery was higher (43.8%, confidence interval (CI): 22.5–66.4), while the success rate of only ART was the lowest (32%, CI: 15.0–52.0) [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“… 12 However, studies have shown that a successful outcome can be achieved after surgery. 23 , 24 Because endometriosis in each woman was located at multiple regions, it affected the reproductive function (fecundity). However, it was difficult to measure this reproductive outcome in this condition, and hence the reproductive outcome was not measured in the current study.…”
Section: Discussionmentioning
confidence: 99%